2022
DOI: 10.1038/s41598-021-04464-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel qualitative test for plasma fibrinogen utilizing clot waveform analysis

Abstract: Plasma fibrinogen is commonly examined by Clauss fibrinogen assay, which cannot distinguish between quantitative and qualitative fibrinogen anomalies. However, our previously reported Clauss fibrinogen assay utilizing clot waveform analysis (Clauss-CWA) provides additional information that contributes to the classification of fibrinogen anomalies. In this study, we adopted the Clauss-CWA method for an autoanalyzer to automatically measure the antigenic estimate (eAg) of fibrinogen in addition to the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…particularly for differential diagnosis of FBG anomalies. 49,[54][55][56][57] A clot waveform in optical changes on a coagulometer indicates the generation of fibrin clot, thus CWA can be considered as an investigation of fibrin clot formation and fibrin(ogen) itself. The Min1 value of CWA in Clauss assay or TT strongly correlates with the antigenic FBG amount rather than the functional amount and can be a surrogate for FBG antigen value.…”
Section: Clot Waveform Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…particularly for differential diagnosis of FBG anomalies. 49,[54][55][56][57] A clot waveform in optical changes on a coagulometer indicates the generation of fibrin clot, thus CWA can be considered as an investigation of fibrin clot formation and fibrin(ogen) itself. The Min1 value of CWA in Clauss assay or TT strongly correlates with the antigenic FBG amount rather than the functional amount and can be a surrogate for FBG antigen value.…”
Section: Clot Waveform Analysismentioning
confidence: 99%
“…54,55 Recent studies demonstrated that the ratio of functional FBG to Min1-derived antigenic FBG estimates in the Clauss assay could be a novel index for differential diagnosis of FBG anomalies 56,57 and showed comparable performance for detecting qualitative FBG abnormalities to the standard method (the combination of Clauss and immunological assays). 49 This novel approach is available on certain analysers, but may not have regulatory approval for clinical use in all regions. where practicable, statistical techniques shall be applied to review the results.…”
Section: Clot Waveform Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A ratio fibrinogen activity / antigen with a cut-off of 0.7 has historically be proposed to distinguish between quantitative and qualitative fibrinogen disorders, but not fully validated 12 . Recently, a cut-off of 0.55 has also been tested 13 . If fibrinogen activity and antigen are disproportionally decreased, a hypodysfibrinogenemia should be considered.…”
Section: Diagnosis Of Hereditary Fibrinogen Disordersmentioning
confidence: 99%
“…In addition, recent data promotes novel approaches for diagnosis of HFDs. Clot wave form from Clauss could have a similar performance to detect dysfibrinogenemia 13 .…”
Section: Diagnosis Of Hereditary Fibrinogen Disordersmentioning
confidence: 99%